Quality and fodder yield of forage black sorghum (Sorghum almum) for silage in mature ages. - Boschini-Figueroa, Carlos (2005)
The study wascarried out to determine the chemical composition andproduction yield of dry matter and nutritional content per areain shoots 91 to 161 days old, and to explore the options forharvest silage. The study took place at the Alfredo VolioMata Experimental Station of the University of Costa Rica.The first samples were taken at 91 days and were re-takenevery 14 days until they were 161 days old. Biomassproduction was measured and the content of dry matter, crudeprotein, ashes, neutral detergent fiber increased as thematurity of the plants increased, to a rate of 0.19%/day inleaves and 0.26%/day in stems, for a 0.22%/day in the wholeplant. The yield of green matter reached its maximum at 135days, the leaves at 121 days, and the stems at 144 days. Themaximum production of dry matter, crude protein and neutraldetergent fiber per hectare was obtained from shoots of 130to 135 days old. The best quality was found at 91 days, with12% of dry matter and 14% crude protein. From that age on,the accumulation of dry matter increased at a rate of 62kg/ha/day (a concentration of 2% every 10 days), of which 48kg were of neutral detergent fiber and an average of 2 kg oflignin. The content of crude protein decreased 1% every 10days.